Developing a Mathematics Instructional Model to Enhance Computational Thinking Skills among Pre-service Mathematics Teachers in Support of the Sustainable Development Goals: A Bibliometric Analysis and Empirical Study - Nitiphoom Adsawatithisakul; Kanyarat Cojorn (Bumi Publikasi Nusantara, 2026)
Computational thinking is essential for preparing future mathematics teachers to address complex problems in digital and sustainable education. This study developed and evaluated a mathematics instructional model for pre-service mathematics teachers using a descriptive bibliometric analysis and an empirical research-and-development approach. Scopus data showed rapid growth in publications on computational thinking from 1987 to 2025, confirming its increasing educational relevance. The model comprised six stages: situation presentation, analysis, association, synthesis, designing and arranging problem-solving procedures, and conclusion. 30 participants completed a one-group pretest-posttest implementation. Results showed significant improvements in decomposition, pattern recognition, abstraction, and algorithm design, supported by positive interview responses. The model provides a framework for computational thinking development and supports SDG-oriented quality teacher education.